Functional changes in the neural retina occur in the absence of mitochondrial dysfunction in a rodent model of diabetic retinopathy. Issue 5 (20th October 2017) - Masser, Dustin R.; Otalora, Laura; Clark, Nicholas W.; Kinter, Michael T.; Elliott, Michael H.; Freeman, Willard M.
Abstract: Diabetic retinopathy is a neurovascular diabetes complication resulting in vision loss. A wealth of literature reports retinal molecular changes indicative of neural deficits, inflammation, and vascular leakage with chronic diabetes, but the mechanistic causes of disease initiation and progression are unknown. Microvascular mitochondrial DNA (mtDNA) damage leading to mitochondrial dysfunction has been proposed to drive vascular dysfunction in retinopathy. However, growing evidence suggests that neural retina dysfunction precedes and may cause vascular damage. Therefore, we tested the hypothesis that neural mtDNA damage and mitochondrial dysfunction are an early initiating factor of neural diabetic retinopathy development in a rat streptozotocin‐induced, Type I diabetes model. Mitochondrial function (oxygen consumption rates) was quantified in retinal synaptic terminals from diabetic and non‐diabetic rats with paired retinal structural and function assessment (optical coherence tomography and electroretinography, respectively). Mitochondrial genome damage was assessed by identifying mutations and deletions across the mtDNA genome by high depth sequencing and absolute mtDNA copy number counting through digital PCR. Mitochondrial protein expression was assessed by targeted mass spectrometry. Retinal functional deficits and neural anatomical changes were present after 3 months of diabetes and prevented/normalized by insulin treatment. No marked dysfunction of mitochondrial activity, maladaptive changes in mitochondrial protein expression, alterations in mtDNA copy number, or increase in mtDNA damage was observed in conjunction with retinal functional and anatomical changes. These results demonstrate that neural retinal dysfunction with diabetes begins prior to mtDNA damage and dysfunction, and therefore retinal neurodegeneration initiation with diabetes occurs through other, non‐mitochondrial DNA damage, mechanisms. Abstract : Neuronal dysfunction precedes traditional vascular defects in diabetic retinopathy disease progression. In this study neuronal mitochondrial status was examined across functional, proteomic, and genomic domains in rats characterized for neural retinal function and structure. Mitochondrial deficits were not evident at a disease timepoint where neural retinal deficits are evident demonstrating that diabetic retinopathy disease initiation occurs through non‐mitochondrial mechanisms.